Contribution to Synchronization and Tracking Modelisation in a CDMA Receiver - Aicha Alami Hassani; Mohcine Zouak; Mostafa Mrabti (Journal of Engineering)
We propose and analyze a noncoherent receiver with PN code tracking for direct sequence code division multiple access (DS-CDMA) communication systems. We employ the delay-lock loop (DLL) architectures for the tracking stage. The choice of DLL parameters is studied with special focus on DS-CDMA communication systems and orthogonality conditions. We described the modeling and simulation of the NCO using hardware description language VHDL. Details of the VHDL implementation are shown.